Much ado about… everything: the plight of Southern European economies from a national competitiveness perspective - Vinhas da Silva, R.; Teixeira, N. (International Interdisciplinary Business-Economics Advancement Journal, 2016)
This paper identifies what are understood to be key drivers of country competitiveness. These are the institutional and structural conditions in an economy that are linked with the attainment of sustainable national competitive advantages through the creation of societal conditions that lead to a collective spirit of healthy competition at the heart of which lay competent organizations. The verification of these institutional and economic conditions of national competitiveness implies the development of a profound understanding of international markets and their aesthetic idiosyncrasies, with clear consequences to the promotion of exported goods and services of high aggregated value and the stimulation of domestic demand as well as the increasing sophistication of domestic business environments.